Understanding motivation and emotion - Reeve, Johnmarshall (Recording for the Blind & Dyslexic, 2001)
[This book] introduces readers to the principles of motivation and emotion by balancing coverage of behavioral, cognitive, and physiological theories with a humanistic approach. [The author covers] recent advances in the field and demonstrates through ... examples how these findings can be applied to readers' daily lives ... By combining a strong theoretical foundation with current research and application, [the author] provides readers with a ... tool for understanding why people do what they do.-Back cover.